Revner, sprækker og skred. Noveller af Helle Helle, Pia Juul og Naja Marie Aidt i 00’erne - Mønster, Louise (Passage - Tidsskrift for litteratur og kritik, 2010)
Louise Mønster: “Splits, Cracks and Slippages: Short Stories by Helle Helle, Pia Juul and Naja Marie Aidt in the 00s” The article analyses short stories by Helle Helle, Pia Juul and Naja Marie Aidt which address family and love relations, and it discusses the way in which they relate to presentations of new Danish literature. It is argued that these short stories are typical for the first decade of the 21th century in their focus on close relations, everyday life and contemporary society, whereas it seems more problematic to align them with the understanding of new Danish literature as a critique of the idea of cultural radicalism and the welfare state.